2008
DOI: 10.1149/1.2917206
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Palladium Oxide-Coated Titanium Anodes for Low-Current-Density Oxygen Evolution

Abstract: A coating composition, ruthenium-palladium oxide, for use on titanium anodes for low-current-density oxygen evolution is presented. Coated titanium anodes hold the promise of producing higher-purity deposits with less power consumption in primary metal electrowinning, but their cost and long-term stability have limited their commercial acceptance. A coating based on stabilized RuO2 with another precious metal, Pd, has been commercially demonstrated, but limited information regarding its structure, electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Furthermore, to enhance the stability of RuO 2 under OER conditions, coupling RuO 2 with several inert or stable oxide components also tends to be an appealing strategy. , For instance, Scott’s group found that Nb 2 O 5 addition stabilized the RuO 2 during the oxygen-evoluting process . Also, insertion of Mn x O y enables the considerable enhancement of both OER activity and stability of RuO 2 , which may be the result of disrupted RuO 2 crystallinity, a modification in the electronic state of Mn, and cracked morphology .…”
Section: Recent Advances In Ru-based Electrocatalysts Toward Water Sp...mentioning
confidence: 99%
“…Furthermore, to enhance the stability of RuO 2 under OER conditions, coupling RuO 2 with several inert or stable oxide components also tends to be an appealing strategy. , For instance, Scott’s group found that Nb 2 O 5 addition stabilized the RuO 2 during the oxygen-evoluting process . Also, insertion of Mn x O y enables the considerable enhancement of both OER activity and stability of RuO 2 , which may be the result of disrupted RuO 2 crystallinity, a modification in the electronic state of Mn, and cracked morphology .…”
Section: Recent Advances In Ru-based Electrocatalysts Toward Water Sp...mentioning
confidence: 99%
“…Therefore, the sample polarization, and consequently their Tafel slope, was amplified. 64,65 This increase in the Tafel slope was more significant in higher fractions of MnO 2 particles in the sample, which is due to higher density of micro-cracks and micro-pores in the samples containing more MnO 2 , which was shown in Figures 4 and 5. Partial evolution of O 3 from the MnO 2 surface may be another reason for the change in Tafel slope of the sample at very high potential.…”
Section: Resultsmentioning
confidence: 79%
“…In another paper from our group [43], it is clearly indicated that life of the anode can be significantly improved by the presence of a thin oxide layer. It is believed that a semiconducting oxide, TiO x, is formed, which improves the stability of the coating, as opposed to an insulating oxide.…”
Section: Stabilitymentioning
confidence: 95%